City and citizenship. An analysis of the strategic plans of urban development from the perspective of gender - Innerarity Grau, Carmen; Sancho, Ana (Investigaciones Feministas (Feminist Research), 2015)
This study focuses on urban planning policies from the standpoint of gender. It stems from the idea that the inclusion of women in public space could be clashing with a design of cities in which the old sexual division of work still weighs heavily. According to it an area of the city corresponds to men (where they work), and another area of the city corresponds to women (where they live). Not only is this an obstacle for the inclusion of women on equal conditions, but also for the conciliation of family and work life.Based on this assumption, the article examines to what degree the strategic and urban plans of Spanish cities (Bilbao, Barcelona, Zaragoza, Malaga and Jaen) take into consideration the gender perspective. Specifically, the study analyses if these plans include the recommendations made by international organisations since the 1990s –mainly the United Nations Human Settlements Programme (UNHabitat)– as regards the transversal inclusion of gender in public policies of urban planning, with the aim of making “conciliatory cities.”